Determinan Motivasi Wajib Pajak Orang Pribadi Dalam Membayar Pajak Penghasilan - Rahmadinia, Putri; Heniwati, Elok; Desyana, Gita (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to analyze the variables that affect the motivation of individual taxpayers inpaying income tax. The research is quantitative and uses a survey method through aquestionnaire. The population in this study were taxpayers residing in Pontianak city consisting of40 samples. The sampling technique used was nonprobability sampling, using the incidentalsampling method. Knowledge of tax regulations partially has no effect on the motivation ofindividual taxpayers to pay income tax. Self assessment system and sanctions have a partiallysignificant effect on the motivation of individual taxpayers to pay income tax. Knowledge of taxregulations, self-assessment system, and tax sanctions simultaneously have a significant effect onthe motivation of individual taxpayers to pay income tax.